Suriname : Technical Assistance Report-National Accounts Statistics Mission. (IMF Staff Country Reports; Country Report ;, 2017)
This Technical Assistance Report discusses measures required to improve the national accounts of Suriname, including consistency with the System of National Accounts 2008. The General Bureau of Statistics (GBS) is expected to implement the recommendations of the IMF mission progressively over a five-year period. Given the staff time wasted on data entry and potential transcription errors, the GBS should give high priority to requesting the Ministry of Finance to provide the Government accounts data in Excel format for 2015 onward. With the support of the Finance Minister, the GBS also needs to implement a formal agreement with the Tax Department to share tax registration data, company income tax returns and sales tax returns.